The micro-zones formation of Zr-based bulk metallic glass composite fabricated by laser 3D printing. (April 2022) - Chang, Zexin; Ge, Yaqiong; Sun, Li; Wang, Wenxian; Zhou, Jun
Abstract: In this study, a Zr-based bulk metallic glass composite (BMGC) was successfully fabricated by laser 3D printing with pre-laid powders. The results showed that the printed bulk metallic glass composite was composed primarily (82.5 vol%) of amorphous phase along with a small fraction of intermetallic compounds. The crystallization characteristics of different micro-zones in the as-printed BMGC were studied. It was found that the molten pool had a fully amorphous structure, while some nanocrystals were found in the re-melted zone, and both dendrites and nanocrystals were observed in the heat affected zone (HAZ). The nanoindentation results showed that the HAZ had the highest hardness, elastic modulus, and elastic recovery compared with the re-melted zone and molten pool zone. The forming mechanism of bulk metallic glasses composite was further studied by finite element analysis of the heating and cooling processes in laser 3D printing.